Development of 4D-printed shape memory polymer actuators for induced-strain shape change - Alshebly, Yousif Saad (2024)
Four-dimensional (4D) printing is gaining interest in the past few years. The prototyping freedom of three-dimensional printing, coupled with the abilities of smart materials and their properties, gave rise to a new field of active structures. The field is still developing in the freedom of control over the shape programming and design reliability, caused by the lack of mathematical models and simulations of the materials. This thesis presents advancement in the shape programming that allows for control of the actuation in actuators, based on printing parameters, structural manipulation, and Joule heating. Fused deposition modelling is used to print all actuators and structures in this research. Printing parameters consisting of the printing speed, passive-to-active layers ratio of prints, printing temperature, layer height, and thickness are tested to investigate the effect they produce on the PLA actuators. A predictive mathematical model is created for all the printing parameters used to control the internal strain in the actuators, with an accuracy of 98% in predicting the bending angle. The model is linked to the simulation methods, allowing simulations of the effect of the parameters. Variable stiffness of the structures by different patterns is used in the assessment, which provides varying effects on the printed structures. A total of 40 different actuator designs are made with each deforming differently because of the patterns used. Design insights are provided by using certain pattern arrangements for specific behaviour. The bending angles are varied between 6.21° and 30.96°, depending on the pattern arrangement used, with very high repeatability. Furthermore, Joule heating of the actuators is done by variating the activation voltage which enables direct control of local activation and allows measurements of thermal and force to be taken on the actuators while it is deforming. After the testing, thermal simulation of conductive materials, with analysis and deformation is performed for validation. The research is finalized with further explorations of concepts in 4D printing, which induce twisting behaviour with high control and thermal-dependent actuation. The thermal-dependant actuators are designed by printing sandwiched layers of different directions, activated at different temperatures, which allows for isolated deformation of each section of layers. The designs and control concepts of the actuators are used to create proofof-concept structures, showing high control of the shape programming and activation. The mechanisms and methods developed can be used and implemented to achieve more reliable 4D-printed designs. As a result, many of these designs improve the fundamental understanding of shape programming in 4D printing.